Mediating vulnerability : comparative approaches and questions of genre - Masschelein, Anneleen; Mussgnug, Florian; Rushworth, Jennifer (Comparative literature and culture., 2021)
Mediating Vulnerability brings vulnerability studies into dialogue with media and genre studies to examine vulnerability from a range of connected perspectives.